The impact of the alterations in caring for COVID-19 patients on Compassion Satisfaction and Compassion Fatigue in Italian nurses: a multi method study - Cosentino, Chiara; Foà, Chiara; Bertuol, Maria; Cappi, Valentina; Riboni, Serena; Rossi, Sandra; Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: During COVID-19 first wave,  healthcare professionals were exposed to a major psychological pressure related to uncertainty, a lack of therapies or a vaccine and shortages of healthcare resources. They developed higher levels of Burnout and  Compassion Fatigue, and similar levels of Compassion Satisfaction. Aim is evaluating in Italian nurses Compassion Satisfaction and Compassion Fatigue and impacting individual and relational variables.Methods: A multi-methods approach was used. Qualitative data were collected through 2 focus group. Quantitative data were collected through a web survey composed by an ad hoc questionnaire developed from the focus group results, the Professional Quality of Life Scale-5 and the Resilience Scale (RS-14).Results: In the qualitative phase 6 categories emerged. From the quantitative analysis the sample reported a moderate level of Compassion Satisfaction, a low level of Burnout  and a moderate level of Secondary Traumatic Stress. Compassion Satisfaction had as predictors resilience (β = .501), followed by feeling part of the team (β = .406) and collaboration with colleagues (β = .386). Secondary Traumatic Stress had as predictors the impact of PPE (β = .269), and feeling Covid-related individual sufferance (β = .212). The only predictor of Burnout was resilience (β = -2195). Conclusions: During COVID-19 first wave Italian nurses were exposed to a higher risk of Secondary Traumatic Stress, mainly impacted by frustration, loss of control, loss of possibility to properly care for patients, and personal threat. Relational and team support had a crucial role in sustaining Compassion Satisfaction.